Chinese myths & legends legends of the universe, deities and heroes - Chen Lianshan (Cultural China series, 2016)
The author believes that ancient Chinese myths and legends were gradually formed on the basis of those of the Huaxia (Han) and by absorbing from the Dongyi (ancient eastern tribes) and the Miaoman (ancient Southern tribes). The author sorted materials from various ancient Chinese books and records, and arranged the myths in order to aid readers' appreciation of the materials. In some chapters, he compares Chinese myths with western ones (especially in the Greek).